Analysis of packaging and Brand Design Assistance Programs by the Ministry of Industry in Improving Product Quality - Restu Fahrunnisa; Dian Marlina Verawati (Profesional Muda Cendekia Publishing, 2021)
Small and Medium Industries (SMIs) in the face of competition have obstacles that are the ability of designing the brand and good packaging. The Directorate General of IKMA provides support for industry players, especially SMIs, to improve the quality of their product packaging through the Brand Design and Packaging Assistance Program for small and medium industries. The purpose of this study is to describe how the program can run in Magelang City, with the limitation of the problems, that are: (1) Procedures for submitting and distributing packages and Brand Design assistance programs as a form of implementing program distribution; and (2) Sustainability after channeling the program in achieving its objectives, specifically improving product quality. The results of this study are from the 24 SMIs, 88% have used a new packaging design and 67% have experienced market expansion. On the other hand, 13% have not used a new design and 33% have not yet experienced market expansion. Through recognition from SMIs who were fortunate to get assistance in the form of physical packaging namely Cheese Stick products with the RAKEDAM Brand, the physical packaging received through the program has characteristics that are able to improve the quality of product.